Classical Madrasah in the Formation of Modern Islamic Education - Shofiah, Robi'atun (Global Education Journal, 2025)
Classical madrasahs play a crucial role in shaping modern Islamic education, particularly in curriculum design, teaching methodology, and student character development. This study aims to analyze the relevance of classical madrasah heritage to modern Islamic education using a qualitative approach through literature review and curriculum document analysis. Primary sources include turats manuscripts, classical Islamic education works, and madrasah curriculum documents, while secondary sources consist of SINTA-indexed academic articles, contemporary books, and related academic publications. The findings indicate that integrating classical values such as tarbiyah, ta’dib, and tazkiyah into modern curricula can achieve a balance between knowledge acquisition, moral development, and 21st-century skills. The modernization of Islamic education is effective when rooted in traditional values, supported by educational technology, and strengthened teacher competence, enabling students to face global challenges without losing their Islamic identity. The study implies that classical madrasahs provide a strategic foundation for developing an integrative education model that combines tradition and pedagogical innovation.